2017
DOI: 10.17507/tpls.0708.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Problem-based Learning on the Indonesian EFL Students’ Environment-related Vocabulary Mastery and Writing Ability

Abstract: Abstract-This study aims at examining the effect of environmental problem-based learning (PBL) on the environment-related vocabulary mastery and writing ability of Indonesian EFL students. Previous studies showed that problem-based learning is a student-centered learning approach that affects students' learning positively and significantly. This study employed a quasi-experimental design by involving two classes of senior high school students, each consisted of 30 students. One class was assigned to be the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…That is to say, they had the same background knowledge. The main finding of this study is in line with a research done by Dyah Christina Iswandari et al, (2017) on the integration of Environmental Education with Problem-based Learning Method which improved students' vocabulary acquisition as the students as they managed to contextualise the words learned in variety of contexts in solving the problem given. The finding based on the marks obtained by the experimental group in this study also shows that the implementation of PBL helps learners to construct knowledge and enhance their learning experience especially in learning language components such as grammar, idioms, literature and vocabulary (Tai & Yuan, 2007).…”
Section: Effects Of Environmental Problem-based Learning On Esl Learnsupporting
confidence: 84%
See 2 more Smart Citations
“…That is to say, they had the same background knowledge. The main finding of this study is in line with a research done by Dyah Christina Iswandari et al, (2017) on the integration of Environmental Education with Problem-based Learning Method which improved students' vocabulary acquisition as the students as they managed to contextualise the words learned in variety of contexts in solving the problem given. The finding based on the marks obtained by the experimental group in this study also shows that the implementation of PBL helps learners to construct knowledge and enhance their learning experience especially in learning language components such as grammar, idioms, literature and vocabulary (Tai & Yuan, 2007).…”
Section: Effects Of Environmental Problem-based Learning On Esl Learnsupporting
confidence: 84%
“…These two studies only focused on the use of PBL in language teaching using different topic aside from environments. However, another study was conducted by Dyah Christina Iswandari et al, (2017) who evaluated the effectiveness of using environmental PBL in language teaching but this study only focused on learners' writing skills. Hence, this study aimed to investigate the effectiveness of Environmental Problem-based Learning, particularly in enhancing ESL learners' English vocabulary achievements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There must be a contextual problem which can stimulate the students to learn the topic with high order thinking skill (HOTS). There are a number of studies in PBL which have been done by many researchers, and one of them is Iswandari (2017). She examines the effect of environmental problem-based learning (PBL) on the environment-related vocabulary mastery and writing ability of Indonesian EFL students.…”
Section: Problem-based Learning In Efl Writing Classesmentioning
confidence: 99%
“…Some of the studies (see Atkinson, 2003;Chen, 2004;Cole, 2012;Elola & Oskoz, 2010;Mahmoud, 2014;Wong, Chin, Chen, & Gao, 2009) revealed that CL could help students develop their English language skills, including EFL writing skills. Furthermore, thare also a number of studies that support the argument which PBL has a powerful effect in EFL learning, including EFL writing (see also Dastgeer, 2015;Iswandari, 2017;Kusmawati & Purwati, 2015;Lin, 2012Lin, , 2015Ng Chin Leong, 2009). However, there is still no study which investigated the integration of cooperative learning and problem-based learning by adding and inserting some pedagogical attempts which directly could influence the improvement of verbal creativity in EFL writing.…”
Section: Introductionmentioning
confidence: 98%